Nickel ions release from orthodontic wires into the oral cavity during orthodontic treatment - R. Almasry; T. F. Kosyreva; A. A. Skalny; I. Katbeh; K. G. Abakeliya; А. S. Birukov; W. N. Kamgang (LLC "Endo Press", 2022)
The medical literature speaks about the influence of the oral cavity environment on the orthodontic archwires containing nickel (Ni) in their structure, causing corrosion of the archwires with the release of nickel ions into the patient's oral fluids leading to its ingestion. If the nickel content in the body exceeds certain proportions, it is considered hazardous and can cause negative effects on the patient's body.Aim. To assess whether the clinical application of round thermoactive nickel-titanium (NiTi) archwires will risk increasing the concentration of (Ni) ions in the patient's oral fluids within first two months of the orthodontic treatment.Materials and methods. The Research was conducted on 17 patients, aged 14 to 27 years, fixed metallic orthodontic appliances were used for treatment. Using an atomic absorption spectrophotometer, oral fluid Samples were analyzed to determine the preliminary рН. Oral fluid samples were gathered from all participants of the study groups during different periods of time, observation was as follows: Before installation of fixed appliances, immediately after fixing the braces and tying up the thermoactive NiTi archwires, in 7 days, one month and two months after fixation.Results. There were no statistically significant differences in concentration of (Ni) ions in first two months of treatment. However, in (25 %) of samples taken from patients in 1-2 months after the beginning of treatment a small increase in concentration of Ni ions (by 7,5 %) was observed.Conclusions. It is improbable that a thermoactive NiTi archwire has a significant additional Ni load for patients undergoing orthodontic treatment.